Pengaruh Politik Hukum Terhadap Sistem Ketenagakerjaan DiIndonesia - Rusito; Doni Adi Supriyo (Cakrawala Hukum: Majalah Ilmiah Fakultas Hukum Universitas Wijayakusuma, 2024)
Legal politics concerns the issue of legal renewal - to understand thedirection of legal politics trying to make rules that will determine how tounderstand the direction of human action. Legal development inIndonesia must first understand the politics of national law adopted inIndonesia. humans act. investigate what changes must be made in the lawthat is currently in effect in order to be in accordance with socialwerkelijkheid (social reality). Basically, labor issues are a social, political,and economic agenda that are quite crucial in modern countries, becauseactual employment issues are not only the relationship between workersand employers, but more broadly also include issues of the economicsystem of a country and at the same time the social system. the politics.Therefore, the economy and politics of a country will greatly determinethe pattern and color